P.T 1/(CosecA-CotA )-1/SinA=1/SinA-1/(CosecA+CotA )

Asked by chethan U | 23rd Jul, 2012, 07:11: PM

Expert Answer:

LHS = 1/(cosecA - cotA) - cosecA
= {(cosecA + cotA)/cosec²A - cot²} - cosecA

we know that cosec²A - cot²A = 1

= cosecA + cotA - cosecA

= cosecA - (cosecA - cotA)

= cosecA - (cosecA - cotA)(cosecA + cotA)/(cosecA + cotA)

= cosecA -(cosec²A - cot²A)/(cosecA + cotA)

= 1/sinA - 1/(cosecA + cotA)  
= RHS

Answered by  | 23rd Jul, 2012, 10:16: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.